Complete genome sequence of the thermophilic Acidobacteria, Pyrinomonas methylaliphatogenes type strain K22T. Issue 1 (December 2015) - Lee, Kevin; Morgan, Xochitl; Power, Jean; Dunfield, Peter; Huttenhower, Curtis; Stott, Matthew
Abstract Strain K22T is the type species of the recently- described genusPyrinomonas, in subdivision 4 of the phylumAcidobacteria (Int J Syst Evol Micr. 2014; 64(1):220–7). It was isolated from geothermally-heated soil from Mt. Ngauruhoe, New Zealand, using low-nutrient medium.P. methylaliphatogenes K22T has a chemoheterotrophic metabolism; it can hydrolyze a limited range of simple carbohydrates and polypeptides. Its cell membrane is dominated byiso- branching fatty acids, and up to 40 % of its lipid content is membrane-spanning and ether lipids. It is obligately aerobic, thermophilic, moderately acidophilic, and non-spore-forming. The 3, 788, 560 bp genome ofP. methylaliphatogenes K22T has a G + C content of 59.36 % and contains 3, 189 protein-encoding and 55 non-coding RNA genes. Genomic analysis was consistent with nutritional requirements; in particular, the identified transporter classes reflect the oligotrophic nature of this strain.